Biopsychosocial Predictors of Cognitive Impairment in the Elderly: A Case-control Study - Roshani, Zahra; Kamrani, Ahmad-Ali A.; Momtaz, Yadollah Abolfathi (Current Psychiatry Research and Reviews, 2020)
Background: Cognitive impairment is one of the most common diseases in the elderly. Several studies have already been conducted to identify related factors, but few have explored all the factors involved in the development of cognitive problems. Objective: The present study aimed to identify significant biopsychosocial predictors of cognitive impairment. Methods: This case-control study was conducted on 535 elderly people referred to Shafa Clinic in the city of Tehran in 2017. The biological factors including serum cholesterol, fasting blood sugar, systolic and diastolic blood pressure, vitamin D, vitamin B12, serum folate, serum homocysteine, height, and weight were measured. The psychological variable in this study was a history of depression that was extracted from the medical records. Social network and social support were measured by LSNS-6 and MOS-SSS questionnaires. The SPSS version 25 was used to analyze the data. Results: The mean age of the control group was 68.4 years (SD = 5.89) and of the case group was 71.5 years (SD = 7.37). The results of multiple logistic regression analysis showed age (AOR=1.05; CI:1.089-1.016, p≤0.05,), Secondary education (AOR=0.51; CI:0.266-0.990, p<0.05,), Tertiary education (AOR=0.41; CI:0.212-0.810, p<0.01,), hypertension (AOR=2.16; CI:3.671-1.266, p<0.01) homocysteine level (AOR=1.09; CI:1.147-1.045, p<0.001,), Hypothyroidism (AOR=0.43; CI: 0.226 0.820, p<0.001,), and depression (AOR=4.5; CI:7.163-2.822, p<0.001) to be significant predictors of cognitive impairment. Conclusion: Results of this study showed that low education level, high blood pressure, high level of homocysteine and depression likely increase the risk of cognitive impairment; also, it was implied that timely screening can identify people at risk. The novelty of the present study is that it used a combination of the biopsychosocial factors to predict unique predictors of cognitive impairment.
Keywords: depression